Hide and Seek: Nanomaterial Interactions With the Immune System - Fadeel, Bengt (Frontiers in Immunology, 2019)
Engineered nanomaterials hold promise for a wide range of applications in medicine. However, safe use of nanomaterials requires that interactions with biological systems, not least with the immune system, are understood. Do nanomaterials elicit novel or unexpected effects, or is it possible to predict immune responses to nanomaterials based on how the immune system handles pathogens? How does the bio-corona of adsorbed biomolecules influence subsequent immune interactions of nanomaterials? How does the grafting of polymers such as poly(ethylene glycol) onto nanomaterial surfaces impact on these interactions? Can ancient immune evasion or ‘stealth’ strategies of pathogens inform the design of nanomaterials for biomedical applications? Can nanoparticles co-opt immune cells to target diseased tissues? The answers to these questions may prove useful for the development of nanomedicines.